Tuning Morphology of Active Layer by using a Wide Bandgap Oligomer‐Like Donor Enables Organic Solar Cells with Over 18% Efficiency. Issue 16 (11th March 2022) - Feng, Wanying; Wu, Simin; Chen, Hongbin; Meng, Lingxian; Huang, Fangfang; Liang, Huazhe; Zhang, Jianqi; Wei, Zhixiang; Wan, Xiangjian; Li, Chenxi; Yao, Zhaoyang; Chen, Yongsheng
Abstract: A wide bandgap oligomer‐like donor CNS‐6‐8 is synthesized and incorporated into the host PM6 :Y6 :PC71 BM system to tune the morphology of the active layer for better device performance. Due to the good miscibility of CNS‐6‐8 with both host donor (PM6 ) and acceptors (Y6 and PC71 BM ), an optimized morphology is achieved with the appropriate phase separation size and enhanced crystallinity, which ultimately leads to more efficient exciton dissociation, charge transport, and lower nonradiative energy loss. As a result, the quaternary device achieves an improved efficiency of 18.07%, with a simultaneously increased open circuit voltage of 0.868 V, fill factor of 78.8%, and the comparable short‐circuit current density of 26.43 mA cm −2 . This work indicates that the favorable 3D interpenetrating network morphology of Y6 containing blend films can be optimized by introducing small amount of a specific molecule with high crystallinity, thus providing an effective strategy to achieve better photovoltaic performance for state‐of‐the‐art Y6 analogs‐based organic solar cells. Abstract : A novel small molecular donor, CNS‐6‐8, is synthesized and incorporated into the state‐of‐the‐art ternary system PM6 :Y6 :PC71 BM to tune the interaction of donors and acceptors. An optimized active layer morphology with appropriate domains and ordered packing is achieved in the PM6 :CNS‐6‐8 :Y6 :PC71 BM blend, affording an excellent power conversion efficiency of 18.07% with synchronously improved V oc, FF, and comparable J sc .